Protein-profile alterations induced by a model of sporadic Alzheimer’s disease - Dimitar Bakalov; Daniela Pechlivanova; Elitsa Stoyanova; Zafer Sabit; Radka Tafradjiiska-Hadjiolova; Lubomir Traikov (Pharmacia)
Alzheimer’s disease (AD), one of the most common forms of dementia, where loss of memory is the first and most characteristic symptom, is emerging as one of the biggest public health burdens in the aging Western society. Although the diagnosis is frequently made with cognitive tests and imaging, the use of biochemical markers in clinical practice is emerging for early diagnosis and prevention. This research aimed to study the effects of the experimental model of AD on the protein profile of the hippocampus and cerebrospinal fluid (CSF). We used an experimental model of sporadic AD induced by intracerebroventricular (ICV) injection of streptozotocin (STZ) in adult male Wistar rats. We performed SDS-PAGE and compared the results to known alterations in the protein profiles of AD patients. This model of AD caused the occurrence of impaired spatial memory and some unexpected protein changes demonstrated by unusual spikes in the densitogram, suggesting posttranslational changes of albumin and other transporter proteins in the hippocampus and CSF. These data suggest that such posttranslational changes may partly contribute to the pathogenesis of AD and can serve as a starting point for further evaluation of the STZ model’s strengths and limitations in studying this disorder.